The implication of internal auditing on the financial performance of commercial banks - Naleba Napandu Fortune (Uganda Christian University, 2024)
Background: Most organizations do not see the value of internal auditing because many see it as a means of snooping on others (Ellis, 2000). Little is known about how internal auditing affects the financial performance of Commercial banks in Uganda, even when it is becoming increasingly clear that internal auditing is a crucial instrument for guaranteeing operational effectiveness, risk management and corporate governance. Objective of the study: The main aim of this study is to examine the influence internal auditing on commercial banks’ financial performance. A case study of Centenary Rural Development Bank, Mapeera Branch. Methodology: The study used a cross sectional study design employing a quantitative research approach and survey data collection method. The target population was comprised of 40 employees from the audit and the risk management departments of staff members who included the internal auditors and risk managers. The study participants were selected using purposive sampling method. Data was then collected through administering the questionnaire and responses were rated on a 5-Likert scale and were coded, cleaned and analyzed for descriptive and inferential (correlational and multiple regression analysis) statistics using SPSS software (version 20.0). Findings: Correlation analysis showed a significant and strong positive correlation (r=0.8, p= 0.000, < 0.005) between corporate governance and financial performance. Furthermore, the relationship between risk management and financial performance was significant although it showed a moderately strong positive correlation (r=0.7, p= 0.000, < 0.05). Results from regression analysis revealed that risk management and corporate governance account for 71% in the variation in financial performance of the bank in the financial performance regression model created and this is significant (R2= 0.705; p=0.000; <0.05). Furthermore, results from the regression revealed a non-significant and positive influence of risk management (β=0.051; p=0.699;>0.05) on financial performance of the bank. In addition, the results from the regression analysis revealed a significant and positive influence of corporate governance (β=0.661; p=0.000;<0.05) on financial performance of the bank.
The effect of internal auditing on the financial performance of commercial banks